O Catch-up tecnológico da China: Uma análise da construç\~ao dos grandes oligopólios de operadoras de telecomunicaç\~oes - Uallace Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This report consists of two parts. In this first part, I analyze the emergence of large oligopolies in the telecommunications sector in China, mainly showing how this was a strategy to strengthen national companies (indigenous companies) that manufacture telecommunications equipment, which became large telecommunications oligopolies in the country. The objective of this work is to analyze China's technological catch-up in the telecommunications sector, using the theoretical and methodological framework of the technology life cycle theory and the Sectoral Innovation System. Corroborating with other works, the hypothesis is defended that China achieved technological catch-up in the telecommunications sector through the strategy of stage-skipping and path-creating, mainly with the prominence of the role of indigenous companies/national capabilities. The contribution of this work has three dimensions that converge with other works on the telecommunications sector in China and at the same time also fill gaps in this debate: i) first dimension, a broader analysis is carried out on the relationship between government/telecommunications operators and companies telecommunication equipment producers, showing the construction of an oligopolistic market structure in the telecommunication operators sector, especially with China Mobile, China Telecommunications Corporation (China Telecom); ii) the second contribution is in relation to the database, incorporating indicators up to 2021 related to the telecommunications sector, such as production, foreign trade, company revenues and investment in research and development (R&D), which indicate the relevance of the telecommunications sector to the Chinese economy, both for its domestic market and for its foreign trade; iii) and the third contribution of this work fills a gap that is not addressed in other works on the subject, which is to analyze the recent geopolitical scenario and its challenges for China, where an international scenario of dispute over technological dominance is increasingly accentuated, and political between the United States and China, with various sanctions imposed by the United States on Chinese companies.
10419/284908
Keywords: L52; O3; F23; 330; technological catch-up; telecommunication; Sectoral System Innovation (SSI); technological life cycles